UNSUR DAPAT MERUGIKAN KEUANGAN NEGARA ATAU PEREKONOMIAN NEGARA PADA PERTANGGUNGJAWABAN TINDAK PIDANA KORUPSI - S. Serbabagus (Faculty of Law, University of Dr. Soetomo, 2017)
The existence problem of corruption in Law Number 31 Year 1999 as amended by Law Number 20 Year 2001 is the formulation of element